2020
DOI: 10.1111/jerd.12648
|View full text |Cite
|
Sign up to set email alerts
|

Creeping attachment: A literature review

Abstract: Objective: Mucogingival surgery has been widely applied in clinics. An interesting phenomenon after mucogingival surgery is the coronal migration of gingival margin, which is described as "creeping attachment." The goal of this review is to summarize the characteristics, significance, mechanism, and manifestation of the creeping attachment after mucogingival surgery and to describe the factors associated with its occurrence. Overview: A total of 82 relevant articles were included in the literature review. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
22

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(51 citation statements)
references
References 58 publications
3
20
0
22
Order By: Relevance
“…This decrease was explained with the displacement of the gingival margin in the coronal direction, namely the creeping attachment. [36][37][38][39] The statistically significant decrease in GRA and CAL at the postoperative 1st, 3rd, and 6th months in both groups compared to the preoperative period in this study is consistent with this literature.…”
Section: Discussionsupporting
confidence: 89%
“…This decrease was explained with the displacement of the gingival margin in the coronal direction, namely the creeping attachment. [36][37][38][39] The statistically significant decrease in GRA and CAL at the postoperative 1st, 3rd, and 6th months in both groups compared to the preoperative period in this study is consistent with this literature.…”
Section: Discussionsupporting
confidence: 89%
“…The most important aspect of the present case report was significant gain in thickness of soft-tissue apical to recession that can further result in longterm stabilization of the covered recession tissue and creeping attachment later on. [12,13] However, 100% RC could not be obtained in the present case due to interdental bone loss and surgical limitation of the operator to reposition the gingival margin coronal to CEJ.…”
Section: Discussionmentioning
confidence: 61%
“…Limited number of patients in each surgical RC technique groups did not allow us to perform a network meta-analysis. In addition, all the included studies had a follow-up ≤12 months, which does not allow assessing the long-term effect of surgical RC techniques on DH, which could be influenced by a possible creeping attachment (Wan et al, 2020). Nevertheless, in one study not included in this systematic review (same population, further results), we observed an improvement in DH in two patients treated, respectively, with tunnel + CTG or CAF + CTG at 2 years of follow-up (Neves et al, 2020) compared to results at 6 months from the included study by Santamaria et al (2017).…”
Section: Discussionmentioning
confidence: 99%